Budesonide prolongs time to relapse in ileal and ileocaecal Crohn's disease. A placebo controlled one year study. Issue 1 (July 1996) - Löfberg, R; Rutgeerts, P; Malchow, H; Lamers, C; Danielsson, A; Olaison, G; Jewell, D; Ostergaard Thomsen, O; Lorenz-Meyer, H; Goebell, H; Hodgson, H; Persson, T; et al.
Abstract : BACKGROUND AND AIMS: To evaluate the efficacy and safety of the topical corticosteroid budesonide, given in an oral controlled release formulation for maintenance of remission in patients with ileal and ileocaecal Crohn's disease (CD). PATIENTS AND METHODS: Out of 176 patients with active CD who had achieved remission (CD activity index score < or = 150) after 10 weeks' treatment with either budesonide or prednisolone, 90 were randomised to continue with once daily treatment of 6 mg budesonide, or 3 mg budesonide or placebo for up to 12 months in a double blind, multicentre trial. Time to symptomatic relapse was calculated using Kaplan-Meier estimates. Morning plasma cortisol was measured at clinic visits and a corticotropin stimulation test was performed after three months of treatment. RESULTS: Thirty two patients were allocated to the 6 mg budesonide group, 31 to the 3 mg group, and 27 to the placebo group. After three months, 19 per cent of the patients in the 6 mg group had relapsed, compared with 45 per cent in the 3 mg group and 44 per cent in the placebo group (p = 0.047). The corresponding results after 12 months was 59 per cent in the 6 mg budesonide group, 74 per cent in the 3 mg group, and 63 per cent in the placebo group (p = 0.44). The median time to relapse or discontinuation was 258 days in the 6 mg group, 139 days in the 3 mg group, and 92 days in the placebo group (p = 0.021). Mean morning plasma cortisol values increased from entry in all three groups with no statistically significant differences at 12 months. All 13 patients remaining in the placebo group after three months had a normal corticotropin stimulation response, compared with 18 of 23 patients in the 6 mg, and 19 of 21 in the 3 mg budesonide groups (p = 0.14). Acne and moon face were slightly more common in the budesonide groups. CONCLUSION: 6 mg budesonide once daily is significantly more efficacious than placebo in prolonging time to relapse in CD, and causes only minor systemic side effects.